Promotion of in situ Forest Farmed American Ginseng (Panax quinquefolius L.) as a Sustainable Use Strategy: Opportunities and Challenges - Liu, Hong; Burkhart, Eric P.; Chen, Vivian Yi Ju; Wei, Xi (Frontiers in Ecology and Evolution, 2021)
The cultivation of wild-harvested plant species is one strategy to achieve species conservation while meeting continued demand. A limitation to this approach for species used in Traditional Chinese Medicine, however, is that products produced under ex situ artificial agricultural conditions are often not a perfect replacement for their wild-collected counterparts, so demand for wild-harvested materials persists. This situation applies to American ginseng, an internationally protected species by the Convention on International Trade of Endangered Species of Wild Fauna and Flora (CITES) since 1975. In this paper, we trace the trade the history and conservation need for American ginseng in North America, including a summary of the development and evolution of in and ex situ cultivation methods. We report results from a preliminary survey of product labeling of American ginseng sold online in China and adjacent regions and provide recommendations for promoting forest farmed ginseng to consumers as a sustainable use strategy. We suggest that the use of CITES’s new “human assisted” production category amongst trade partners, coupled with “green” product certification and e-commerce platforms, provides a new opportunity to encourage consumption of wild-cultivated rather than wild ginseng in east Asia, and the continued development of ginseng forest farming and supply transparency mechanisms in the eastern U.S.